Lithological structure of the Galápagos Plume. (15th October 2013) - Vidito, Christopher; Herzberg, Claude; Gazel, Esteban; Geist, Dennis; Harpp, Karen
<x xml:space="preserve">Abstract</x> [1] We have measured Ni, Ca, and Mn in olivine phenocrysts from volcanoes in the Galápagos Archipelago to infer the mantle source lithologies. Results show that peridotite is the dominant source lithology for Fernandina, Floreana, Genovesa, Wolf Island, and Darwin Island. These volcanoes largely characterize the PLUME, WD, FLO, and DUM Nd, Sr, and Pb isotopic endmembers of Harpp and White (2001). Volcan Wolf, Alcedo, Marchena, and Cerro Azul, also produced from the melting of peridotite sources, have isotopic compositions that can be defined by mixing of the four isotopic endmembers. Our analysis suggests that peridotite was present in the sources of the volcanoes covered in this study and therefore is the dominant source lithology of the Galápagos plume. Pyroxenite melting is generally focused in two isotopically distinct domains: Roca Redonda, Volcan Ecuador, and Sierra Negra in the enriched western part of the archipelago and Santiago, Santa Cruz, and Santa Fe in the depleted east. One implication of this finding is that the Western and Eastern Pyroxenite Domains represent two separate bodies of recycled crust within the Galápagos mantle plume. Furthermore, both isotopically enriched and depleted domains of the archipelago were generated from mixtures of peridotite and pyroxenite. This suggests that there is no relationship between the source lithology of the Galápagos plume and its isotopic characteristics. The identification of peridotite‐source melting in volcanoes with isotopic characteristics that have been attributed to recycled crust points to the importance of mixing in OIB genesis, consistent with studies in the Canary Islands.